Monocytic microRNAs—Novel targets in atherosclerosis therapy - Euler, Gerhild; Parahuleva, Mariana; Justus Liebig University Giessen (My University, 2024)
Atherosclerosis is a chronic proinflammatory disease of the vascular wall resulting in narrowing of arteries due to plaque formation, thereby causing reduced blood supply that is the leading cause for diverse end-organ damage with high mortality rates. Monocytes/macrophages, activated by elevated circulating lipoproteins, are significantly involved in the formation and development of atherosclerotic plaques. The imbalance between proinflammatory and anti-inflammatory macrophages, arising from dysregulated macrophage polarization, appears to be a driving force in this process. Proatherosclerotic processes acting on monocytes/macrophages include accumulation of cholesterol in macrophages leading to foam cell formation, as well as dysfunctional efferocytosis, all of which contribute to the formation of unstable plaques. In recent years, microRNAs (miRs) were identified as factors that could modulate monocyte/macrophage function and may therefore interfere with the atherosclerotic process. In this review, we present effects of monocyte/macrophage-derived miRs on atherosclerotic processes in order to reveal new treatment options using miRmimics or antagomiRs.
Keywords: ddc:610